Mobile screen time, sleep quality, motor coordination, and cognitive functions in newly diagnosed epileptic patients - Kirubanand N; Kavitha S; Vikash Sharma; Sai Sailesh Kumar Goothy; Rohit Singh Chouhan (Asian Journal of Medical Sciences, 2025)
Background: Epilepsy is a chronic condition of recurrent seizures that can also vary from brief and nearly undetectable symptoms to periods of vigorous shaking and convulsions. Understanding all these causative factors with epilepsy is very essential for early diagnosis and management of epilepsy effectively. Hence, the present study was undertaken to observe screen time, sleep quality, motor coordination, eating behavior, and cognitive functions in newly diagnosed epileptic patients. Aims and Objectives: The present study was undertaken to observe screen time, sleep quality, motor coordination, eating behavior, and cognitive functions in newly diagnosed epileptic patients. Materials and Methods: The present cross-sectional study recruited 44 newly diagnosed male and female epileptic patients during the study period. 44 age and gender-matched controls were also recruited. Screen time was recorded using digital well-being application installed in the mobile phone which provides average mobile screen time data of the individual. Sleep quality was assessed using insomnia severity index (ISI) questionnaire. 100 pin dexterity test was used to assess the motor coordination. Cognitive functions were assessed using spatial and verbal memory test. Results: Significantly higher mobile screen time duration (P=0.0032) and higher insomnia severity scores (P=0.0059) were observed in the cases. 100 pin dexterity test duration was not significantly different among the cases and controls. Spatial memory (P=0.0306) and verbal memory (P=0.0212) scores were significantly higher in cases than controls. Conclusion: The study results present longer mobile screen time, longer duration for 100 pin dexterity test, higher ISI scores, and lower memory scores in the newly diagnosed epileptic patients. Hence, these factors have to be considered in the diagnosis and prognosis of the epilepsy.